2017
DOI: 10.1111/cdev.12720
|View full text |Cite
|
Sign up to set email alerts
|

Preschoolers Continually Adjust Their Epistemic Trust Based on an Informant's Ongoing Accuracy

Abstract: Children aged 4-7 years (N = 120) played four rounds of a find-the-sticker game. For each round, an informant looked into two cups and made a claim about which cup held a sticker. At the end of each round, children guessed the sticker's location, and then the sticker's actual location was revealed. For three of the rounds, the informant accurately reported the sticker's location. But critically, for one round-either Round 1, 2, or 3-she was inaccurate. Children continually adjusted their trust in the informant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 44 publications
7
36
0
Order By: Relevance
“…Our results agree with a recent study in which 5-year-olds updated their trust in an informant's claim from extended observation of behaviour (Ronfard & Lane, 2018). Children guessed, over 4 trials, the location of a sticker under cup A or B, based on what an informant told another agent; this informant was inaccurate on one of 4 trials.…”
Section: Children Can Update Mentally Represented Beliefssupporting
confidence: 90%
See 2 more Smart Citations
“…Our results agree with a recent study in which 5-year-olds updated their trust in an informant's claim from extended observation of behaviour (Ronfard & Lane, 2018). Children guessed, over 4 trials, the location of a sticker under cup A or B, based on what an informant told another agent; this informant was inaccurate on one of 4 trials.…”
Section: Children Can Update Mentally Represented Beliefssupporting
confidence: 90%
“…In Ronfard and Lane's (2018) work, children saw complex behaviour, but each child judged only one sequence, so the data give limited information on process. The present data are complementary, with children judging multiple, simpler sequences, which allows process analysis.…”
Section: Children Can Update Mentally Represented Beliefsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, research on children's understanding of traits has shown that preschool‐aged children have difficulties grasping that traits remain stable and are predictive of behavior over time and across different contexts (Rholes & Rubel, ; Ruble & Dweck, ). Furthermore, preschool‐aged children need more behavioral examples to make trait attributions, especially negative ones (Boseovski & Lee, ; Heyman & Dweck, ; Ronfard & Lane, ). Thus, perhaps the 4‐year‐olds in our study were not as proficient as the 5‐year‐olds at predicting the transgressors’ future behaviors (e.g., who would be likely to help or hurt them in the future) based on the behaviors they had just witnessed, and they may also have had difficulty generalizing information about the transgressors to the new context of distributing resources.…”
Section: Discussionmentioning
confidence: 99%
“…The format of these questions made certain assumptions about children's responses (e.g., the question “Whom are you more upset with?” presumed that they were upset) and forced participants to choose one of the transgressors when in fact children may have wanted to choose both or neither. Indeed, research has shown that children are less discriminating on tasks where they are presented with one individual rather than two contrasting individuals (Boseovski & Lee, ; Ronfard & Lane, ). While we acknowledge that there are limitations in using forced‐choice questions, we chose to use them because as a first step in investigating children's forgiveness, we believed it was important to demonstrate that children can discriminate between remorseful and unremorseful transgressors and that they do show a systematic preference at least within this more constrained format.…”
Section: Discussionmentioning
confidence: 99%